(untitled) (Bioscience Journal, 2017)
The aim of this estudy was to establish the levels of serum total protein, albumin, globulin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), calcium, phosphorus, urea, creatinine, bilirubin and glucose during pregnancy in agoutis. Animals: Twelve pregnant agouti from the Center for the Study and Preservation of Wild Animals (CSPWA) of the Federal University of Piauí (UFPI) were used in this research. After identification of the estrus, the day of the coverage was confirmed by means of vaginal cytology with the visualization of spermatozoa (day zero) and confirmation of pregnancy by ultrasonographic examination after 15 days. Blood samples were collected by lateral saphenous vein puncture after physical restraint, every 10 days until the end of pregnancy, for biochemical analyzes. A completely randomized experimental design was used and the means compared by the Duncan test at 5% probability using the SAS (Statistical Analysis System). The results of the biochemical analysis of total protein, albumin, globulin, urea, creatinine, calcium, phosphorus, serum ALT, glucose, AST, total bilirubin, direct bilirubin and indirect bilirubin in pregnant agouti (Dasyprocta prymnolopha) did not differ when compared to nonpregnant females. The serum biochemical levels during pregnancy in agoutis, except for calcium and phosphorus, were unchanged compared to those found in the non-pregnant adult animal, as occurs in other species. The changes during pregnancy reflect the physiology and biology of wild species, elucidating information about the biochemical parameters during pregnancy, thus characterizing the animal as a benchmark for comparisons with other species, extolling its importance both for nature conservation and production in capivity.